Wireless charging system using magnetic resonant coupling - Somasundaram, Kowsik Kumar (2019)
Wireless charging is the transmission of power through air medium without contact. The wireless charging using magnetic resonant coupling is for charging the electric vehicles with the help of the resonant coupling. The resonant coupling is used especially for the efficiency purpose. An oscillating current within a coil (transmitting coil) results in a magnetic field around the coil. When placing with another coil (receiving coil), the magnetic field then induces a current in that coil. In this project, the investigation of wireless charging using magnetic resonant coupling in electric vehicles (EVs) was conducted. The working condition was studied and the research work is carried out for better efficiency. The circuits in this project employ the use of DC/AC oscillators, resonating capacitors, AC/DC rectifiers, and DC/DC buck converters. Simulation of wireless charging using magnetic resonant coupling under different operating conditions using MATLAB/Simulink will be studied. Resonating capacitors which are the resonant circuits, which are used to reduce the ripples. Simulink is used for designing the model, simulating it and examining the output efficiency.